Development of novel antibodies for detection of mobile colistin-resistant bacteria contaminated in meats. Issue 1 (December 2018) - He, Xiaohua; Mavrici, Daniela; Patfield, Stephanie; Rubio, Fernando
Abstract The recent discovery and rapid spread of mobile colistin-resistant gene, mcr -1, among bacteria isolated from a broad range of sources is undermining our ability to treat bacterial infections and threatening human health and safety. To prevent further transfer of colistin resistance, practical and reliable methods formcr -1-containing bacteria are need. In this study, standards and novel polyclonal and monoclonal antibodies (mAbs) against MCR-1 were developed. Among nine mAbs, three were MCR-1 specific and six cross-reacted with both MCR-1 and MCR-2. A sandwich enzyme-linked immunosorbent assay (ELISA) was established using the polyclonal antibody as a capturer and the mAb MCR-1-7 as a detector. The assay had a limit of detection of 0.01 ng/mL for MCR-1 and 0.1 ng/mL for MCR-2 in buffer with coefficients of variation (CV) less than 15%. When applied to ground beef, chicken and pork, this ELISA identified samples inoculated with less than 0.4 cfu/g of meat, demonstrating its strong tolerance to complex food matrices. To our knowledge, this is the first immunoassay developed for MCR-1 and MCR-2. It should be useful for prompt and reliable screening of meat samples contaminated with plasmid-borne colistin-resistant bacteria, thus reducing human risk of foodborne infections with possibly no antibiotic treatment options.